ECOSYSTEM OF ENTREPRENEURSHIP: INNOVATIVE STRATEGIES AND INNOVATIVE CHANGES - Паляниця, Владислав Вадимович (Journal of Strategic Economic Research, 2024)
In today's dynamic world, entrepreneurship has become an important engine of economic development and social change. In the conditions of globalization and rapid technological progress, traditional business models and strategies are gradually fading into the background, giving way to new approaches and innovations. The entrepreneurship ecosystem, consisting of diverse actors such as startups, investors, academic institutions and government bodies, is undergoing profound transformations that provide new opportunities and challenges for entrepreneurs. The purpose of the presented work is to determine the main features of the construction of a modern ecosystem in the conditions of innovative changes and the implementation of an innovative strategy. Methods used in the work: analysis method, synthesis method, induction method, deduction method, logical method, comparison method, generalization method, tabular method, graphic method. The research also revealed that innovative strategies that are actively implemented in this ecosystem have become critical for ensuring competitiveness and sustainable business development. They cover a variety of aspects, from the integration of the latest technologies, such as artificial intelligence and blockchain, to changing organizational structures and cultural approaches. These strategies allow not only to adapt to rapidly changing market conditions, but also to create new trends and opportunities. At the same time, innovative changes taking place within the entrepreneurial ecosystem are forming new paradigms for conducting business. They include social and environmental aspects affecting corporate responsibility and social inclusion. Organizational changes, such as the introduction of agile management methodologies and cross-functional teams, also play a key role in adapting enterprises to new challenges. Therefore, studying innovation strategies and changes in the entrepreneurial ecosystem is important for understanding how today's companies shape their future, adapt to challenges and take advantage of new opportunities. This analysis will allow a better understanding of what factors influence the development of entrepreneurship and how innovation can become a driving force for achieving success in today's economic environment.